Peningkatan Kualitas Produksi Ikan Asap di Rumah Produksi Kampung Rawa Jaya Tobelo Melalui Inovasi Alat Pengasapan Ikan Sari Waruna - Indrayana, I Putu Tedy; Puni, M S; Manumpil, A; Huragana, Y M (International Journal of Community Service Learning, 2020)
This community service aims to provide innovation in the fish smokehouse in Rawa Jaya Tobelo. The target of this activity is to be able to improve the quality of smoked fish production and packaging so that it has the potential to increase the selling value of the product. This activity was carried out for 5 months by implementing a collaborative strategy between the service team and the partner community. The focus of this service is (1) manufacturing "Sari Waruna" smokehouse and (2) technical product packaging assistance. "Sari Waruna" smokehouse was successfully built within 3 weeks. This activity has succeeded in developing the "Sari Waruna" smokehouse which has a production capacity of 100 smoked fish. Fumigation only lasts for 3 hours so it is more fuel-efficient. The texture of the meat from the smoked fish is tastier, the color is bright reddish-brown and clean. Smoked fish can last for 4 days. The packaged smoked fish has the potential to be marketed out of Tobelo. The partner community responded positively to this community service activity because it supported the development of smoked fish business going forward.